WIMA: An Open-Source API for efficient Image Transmission on Wireless Sensor Networks - De Sousa, Janislley Oliveira; Santos, Ricardo Nogueira; P. Júnior, João Danilo; Lima, Moysés M. (Anais do Congresso Latino-Americano de Software Livre e Tecnologias Abertas (Latinoware); 2024: Anais do XXI Congresso Latino-Americano de Software Livre e Tecnologias Abertas, 2024)
This paper explores the integration of image sensors into Wireless Sensor Networks (WSN) for Internet of Things (IoT) applications, an area currently limited by technical constraints. It introduces WSN Image API (WIMA), an open-source and adaptable API designed to unify and simulate the stages of image transmission. Developed and designed on the Contiki-NG/Cooja platform, WIMA has demonstrated its viability through simulations of use cases, validating its efficacy in supporting image transmission in WSN environments. The API offers a standardized approach for incorporating image data into WSN, addressing a significant gap in current methodologies to simulate this scenario for IoT applications. Future work will focus on deploying WIMA in real-world scenarios to evaluate and improve its image transmission capabilities.